(untitled) (The Macau Ricci Institute Journal, 2023)
The essence of spirituality carries important meanings: first, spirituality refers to ‘believing life’ (Vida creyente). Second, spirituality relates to discernment in the context of Christian faith (lo doctrinal) and pastoral work (lo pastoral) (Ashley, 2017). Customarily, spirituality can be found in different religions, even though Ignatian spirituality is deeply rooted in the formation of the Society of Jesus (Allen & Williams, 2020; Nullens, 2019). Under the teaching of the Jesuits, spirituality comprises finding God in all things, the Spiritual Exercises, discernment, and the Constitutions (The Society of Jesus, 2021). In this paper, we will discuss the distinctive discourse of spirituality, “Metanoia,” in Jesuit Higher Education in the Asian context. After collecting data from 30 semi-structured in-depth interviews of 30 Presidents, faculty members, and senior administrators from four Jesuit Universities in Asia over a period of nine months from September 2020 – June 2021, about Jesuit Educational Leadership, in my DPhil(Ph.D.) studies at The University of Oxford, we have found the distinctive characteristics of spirituality Metanoia define commitment in Asian Jesuit Higher Education from the top level of management, structured Jesuit programs, and spirituality. The original names of all the interviewees are anonymized so as to protect the confidentiality of the interviewees. All the interviewees’ names used in this paper are not real. Snowballing sampling method was adopted in this study.